Personality and power : builders and destroyers of modern Europe - Kershaw, Ian (Penguin Press, 2022)
"From one of the leading historians of twentieth-century Europe and the author of the definitive biography of Hitler, Personality and Power is a masterful reckoning with how character conspired with opportunity to create the modern age's uniquely devastating despots-and how and why other countries found better paths. The modern era saw the emergence of individuals who had command over a terrifying array of instruments of control, persuasion and death. Whole societies were reshaped and wars were fought, often with a merciless contempt for the most basic norms. At the summit of these societies were leaders whose personalities somehow enabled them to do whatever they wished, regardless of the consequences for others. Ian Kershaw's new book is a compelling, lucid and challenging attempt to understand these rulers, whether those operating on the widest stage (Lenin, Stalin, Hitler, Mussolini) or with a more national impact (Tito, Franco). What was it about these leaders, and the times in which they lived, that allowed them such untrammelled and murderous power? And what brought that era to an end? In a contrasting group of profiles-from Churchill to de Gaulle, Adenauer to Gorbachev and Thatcher to Kohl)-Kershaw uses his exceptional skills as an iconic historian to explore how strikingly different figures wielded power"--